Implementasi Kurikulum 2013 Pada Siswa Dan Siswi Di SD Darussalam Agats Asmat Papua Selatan - Wardani, Ayu Pramudia Kusuma; Wardani, Moni Kusuma; Hidayati, Nurlailli; Khuriyah, Khuriyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine teachers' understanding of implementing the 2013 curriculum at SD Darussalam Asmat South Papua. The research method used is a form of qualitative descriptive research. Sources of research data are school principals and teachers. The results of the study show that teachers' understanding of the 2013 curriculum is quite good, but with any approach to students broadly and deeply, it is still not visible because there are still some students who choose to be busy playing and not focus on learning. To design learning activities the teacher can create and teach by the lesson plan and syllabus that has been made, and can carry out learning activities very well, for example being able to describe the topic of discussion of subjects into interesting information and easily understood by most students, being able to adjust class when learning activities take place, can evaluate students' learning progress very well, such as carrying out written or oral test assessments, analyzing learning outcomes to determine the level of learning completeness, being able to involve themselves to develop students' potential and being able to identify students' talents and interests very well, such as knowing students' interest in learning or not.